The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fphys.2023.1219252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multi-professional intervention on body composition, physical fitness and biochemical markers in overweight COVID-19 survivors: a clinical trial

Ana Flávia Sordi,
Maurício Medeiros Lemos,
Déborah Cristina de Souza Marques
et al.

Abstract: Introduction: The sequelae post-COVID can affect different systems. In this sense, considering the multi-factorial etiology of COVID-19, multi-professional interventions could be a relevant strategy for recovery health indicators.Objective: This study aimed to investigate the effects of multi-professional intervention on body composition, physical fitness, and biomarkers in overweight COVID-19 survivors with different symptomatology.Methodology: A non-randomized parallel group intervention included 69 voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Rehabilitation is a multidisciplinary intervention that aims to improve functional capacity, increase the quality of life, facilitate social reintegration after hospitalization, reduce persistent symptoms, and improve the ability to perform the activities of daily living [ 112 ]. Sordi et al [ 113 ] evaluated the effect of a multi-professional intervention (nutritional, psychoeducational, and physical exercise intervention) on body composition, physical fitness, and biochemical markers in overweight COVID-19 survivors (BMI ≥ 25 kg/m 2 ) with different symptoms. After the interventions, the authors reported that the moderate COVID-19 group showed improvement in the dynamic muscle strength of the lower and upper limbs, maximum lumbar isometry—traction force, flexibility, and markers such as albumin, CRP, fasting glycemia, and triglycerides; for the severe COVID-19 group, improvements were seen in the dynamic muscle strength of the lower limbs and lower CRP and triglyceride values; for the control group, improvements were seen in abdominal repetitions, CRP, fasting glucose, TC, and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation is a multidisciplinary intervention that aims to improve functional capacity, increase the quality of life, facilitate social reintegration after hospitalization, reduce persistent symptoms, and improve the ability to perform the activities of daily living [ 112 ]. Sordi et al [ 113 ] evaluated the effect of a multi-professional intervention (nutritional, psychoeducational, and physical exercise intervention) on body composition, physical fitness, and biochemical markers in overweight COVID-19 survivors (BMI ≥ 25 kg/m 2 ) with different symptoms. After the interventions, the authors reported that the moderate COVID-19 group showed improvement in the dynamic muscle strength of the lower and upper limbs, maximum lumbar isometry—traction force, flexibility, and markers such as albumin, CRP, fasting glycemia, and triglycerides; for the severe COVID-19 group, improvements were seen in the dynamic muscle strength of the lower limbs and lower CRP and triglyceride values; for the control group, improvements were seen in abdominal repetitions, CRP, fasting glucose, TC, and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…Large epidemiology has also documented that physical activity was inversely associated with severe COVID-19 ( 46 ). Physical activity is accounted as an efficient intervention for reversing an inflammatory process ( 47 ) and cardioprotective effect in COVID-19 survivors ( 43 ). In the context of current review, sufficient physical activity (≥150 min a week of moderate intensity) can impede viral entry to the targeted cell by increase in plasma soluble angiotensin-converting enzyme 2 (sACE2), which can bind to SARS-CoV-2 ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Lemos et al (2022) evaluated body composition and cardiorespiratory fitness in individuals with overweight or obesity after COVID-19 and found that excess fat deposition creates a chronic low-grade inflammatory environment. In turn, this environment can dysregulate the immune and endocrine systems (Manrique-Acevedo et al, 2020), contributing to various other comorbidities and affecting functional capacity and health-related quality of life (Sordi et al, 2023;Ryal et al, 2023;Perli et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These findings emphasize the importance of addressing the topic with greater attention, aiming to understand the effects of obesity after COVID-19 infection and implementing interventions to improve the health and well-being of these patients. Among the comorbidities, previous studies have reported that obesity is one of the risk factors for the worsening of COVID-19 (Kang et al, 2020;Stefan et al, 2021;Lemos et al, 2022;Perli et al, 2023;Sordi et al, 2023;Ryal et al, 2023) and that individuals with obesity infected with COVID-19 had a higher mortality rate compared to non-obese individuals (Kang et al, 2020). Indeed, the quarantine period, adopted as a control measure during the pandemic, is a predictive factor for symptoms of acute stress disorder, anxiety, depression, insomnia, exhaustion, and post-traumatic stress disorder (Brooks et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation